2023
DOI: 10.21203/rs.3.rs-2953875/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Looking under the lamp-post: quantifying the performance of contact tracing in the United States during the SARS-CoV-2 pandemic

Abstract: Contact tracing forms a crucial part of the public-health toolbox in mitigating and understanding emergent pathogens and nascent disease outbreaks. Contact tracing in the United States was conducted during the pre-Omicron phase of the ongoing COVID-19 pandemic. This tracing relied on voluntary reporting and responses, often using rapid antigen tests (with a high false negative rate) due to lack of accessibility to PCR tests. These limitations, combined with SARS-CoV-2’s propensity for asymptomatic transmission… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…For instance, one study during the COVID-19 pandemic in the United States found that 68% of positive index cases reported having 0 contacts, undermining the reliability of this approach [ 35 ]. In a previous work, we combined data from multiple contact tracing studies using a Markov model, to estimate that in the United States, the chance of identifying a positive contact of a positive index case was about 1.65% (assuming the use of PCR tests) [ 36 ]. In addition to the clear problems this poses for infection control, this incompleteness in basic contact tracing data leads to a question of just how accurate our inferences about the transmission dynamics of SARS-CoV-2 really are.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one study during the COVID-19 pandemic in the United States found that 68% of positive index cases reported having 0 contacts, undermining the reliability of this approach [ 35 ]. In a previous work, we combined data from multiple contact tracing studies using a Markov model, to estimate that in the United States, the chance of identifying a positive contact of a positive index case was about 1.65% (assuming the use of PCR tests) [ 36 ]. In addition to the clear problems this poses for infection control, this incompleteness in basic contact tracing data leads to a question of just how accurate our inferences about the transmission dynamics of SARS-CoV-2 really are.…”
Section: Introductionmentioning
confidence: 99%